Effects of dietary supplementation probiotic complex on growth performance, blood parameters, fecal harmful gas, and fecal microbiota in AA+ male broilers - Zou, Qiangqiang; Fan, Xinyan; Xu, Yunhe; Wang, Tieliang; Li, Desheng (Frontiers in Microbiology, 2022)
In this study, Bacillus subtilis, Clostridium butyricum and Enterococcus faecalis were made into a probiotic complex (PC). The PC was supplemented in AA+ male broilers’ diets to investigate the effects of PC on broiler growth performance, carcass traits, blood indicators, harmful gas emissions in faeces and microbiota. Three hundred and sixty 1-day-old AA+ male broilers with an average initial body weight (data) were randomly divided into 3 dietary treatments of 6 replicates each, with 20 birds per replicate. The control group (T0) was fed a basal diet, while the test groups (T1 and T2) were supplemented with 0.025% and 0.05% PC in the basal diet respectively. The trail was 42 days. The results showed that the supplementation of 0.05% PC significantly (P < 0.05) improved average daily gain (ADG) and average daily feed intake (ADFI) of broilers from 22-42 days and 1-42 days. Compared to the control group, the breast rate was significantly higher in T2, and the thymic index was significantly higher than that in T1 treatment (P < 0.05). The addition of PC had no significant effects on antibody potency in broiler serum (P > 0.05), but significantly increased albumin and total protein content in serum (P < 0.05). The addition of PC reduced H2S and NH3 emissions in the faeces; the levels of E. coli and Salmonella in the faeces were significantly reduced and the levels of Lactobacillus were increased. And the most significant results were achieved when PC was added at 0.05%. Correlation analysis showed a significant positive correlation (P < 0.05) between the levels of E. coli and Salmonella and the emissions of H2S and NH3. Conclusion: Dietary supplementation with a 0.05% probiotic complex could improve the growth performance of broilers and also reduced faecal H2S and NH3 emissions, as well as faecal levels of E. coli and Salmonella, and increased levels of Lactobacillus. Thus, PC made by Bacillus subtilis, Clostridium butyricum and Enterococcus faecalis is expected to be an alternative to antibiotics. And based on the results of this trial, the recommended dose for use in on-farm production was 0.05%.